Asymmetric Shaped-Pattern Synthesis for Planar Antenna Arrays - T. M. Bruintjes; A. B. J. Kokkeler; G. J. M. Smit (International Journal of Antennas and Propagation)
A procedure to synthesize asymmetrically shaped beam patterns is developed for planar antenna arrays. As it is based on the quasi-analytical method of collapsed distributions, the main advantage of this procedure is the ability to realize a shaped (null-free) region with very low ripple. Smooth and asymmetrically shaped regions can be used for Direction-of-Arrival estimation and subsequently for efficient tracking with a single output (fully analog) beamformer.